Profesional Competence of English Teachers' Alumni of IAIN Bengkulu in the Era of Industrial Revolution 4.0 - Haryanto, Endang; Zasrianita, Fera (Linguistic, English Education and Art (LEEA) Journal, 2024)
The purpose of this study is to examine the professional competence of IAIN English program alumni in using information technology in the 4.0 era in English learning at secondary school. The research method used in this study is descriptive qualitative and the subjects in this study were English teachers who are alumni of IAIN Bengkulu who teach at the junior high school level in Seluma, Manna and Kaur Regencies. Data analysis in this research is done by classifying and comparing data from observation, interview, and documentation, and data analysis includes data reduction, data presentation, and conclusion drawing. Based on the result of the study, the data showed that the level of digital literacy skills in using MLS is considered being advanced category only 30% of alumni. Furthermore, the ability of teachers to make MLS learning is only 20% as well as the ability to use learning methods and techniques. Furthermore, among alumni who teach are 30% who experienced in training 20% and the only 10 % of the teachers who developed their own teaching materials on MLS were only 10%. To sum up, most of the teachers who were the alumni were not capable enough in personalizing technology to the classroom. Hence a recommendation it would be necessary for university to prepare their alumni with qualified experiences during their study. Keywords: English, Competence, Professional Teacher